Traditional intracytoplasmic sperm injection provides equivalent outcomes compared with human zona pellucida-bound selected sperm injection. Issue 4 (November 2014) - Casciani, Valentina; Minasi, Maria Giulia; Fabozzi, Gemma; Scarselli, Filomena; Colasante, Alessandro; Lobascio, Anna Maria; Greco, Ermanno
Summary The capability of human zona pellucida (ZP) to bind selectively to normal functional sperm with normal chromatin has been reported widely in the literature. The aim of this study was to evaluate whether ZP–binding sperm selection may represent a method to retrieve superior spermatozoa for intracytoplasmic sperm injection (ICSI). Patients were divided into two groups: a ZP-ICSI and a conventional ICSI group. In the ZP-ICSI group, spermatozoa for injection were selected after ZP–sperm incubation and spermatozoa that were tightly bound to the ZP were used for ICSI (ZP-ICSI). Clinical outcomes of ZP-ICSI were compared with the outcomes of traditional scientist-selected sperm injection (conventional ICSI). Results did not show any significant difference in fertilization, pregnancy, implantation and take-home-baby rates between conventional ICSI and ZP-ICSI. However, when data relative to patients who received ZP-ICSI were analyzed, an interesting result was observed: higher sperm concentration and morphology correlated with higher ZP–sperm binding. Additionally, patients with higher ZP–sperm binding seem to have improved pregnancy and take-home-baby rates. In conclusion, this study shows that ZP-ICSI is not a superior method compared with conventional ICSI. However, clinical ICSI outcomes were apparently improved in the presence of good ZP–sperm binding. We therefore speculate that sperm competence to ICSI could be reduced when the sperm's ability to bind the ZP is impaired.